Experience of Identifying the Specifics of Everyday Linguistic Consciousness of Russians according to Associative Dictionaries of the XX-XXI Centuries - S. P. Vasilyeva (Научный диалог, 2020)
The article is devoted to comparing data on the results of associative experiments of different years. The main focus is on the conceptual core - the first ten words with the most associative links. It is reported that in 2013-2017, researchers of the Krasnoyarsk State Pedagogical University named after V. P. Astafiev, with the support of scientific foundations, prepared the “Electronic associative dictionary of Yenisei Siberia”, which includes 29,550 associative fields based on the results obtained when 1000 respondents were presented (incentives were proposed by the team of the ethnopsycholinguistics sector of the Institute of Atomic Energy RAS under the direction of N. V. Ufimtseva). The article compares the obtained data with the materials of the conceptual core of other associative dictionaries of the Russian language of the XX-XXI centuries, such as the “Dictionary of associative norms of the Russian language” by A. A. Leontyev, “Russian Associative Dictionary” edited by Yu. N. Karaulov, “Russian regional associative dictionary-thesaurus” by G. A. Cherkasova, N. V. Ufimtseva. It is proved that the data of associative dictionaries indicate a change in indicators on the scale of values of linguistic consciousness of the Russian language native speakers. An attempt was made to identify the specifics of the everyday linguistic consciousness of Russians in a geographically limited community. The conclusion is made that the changes in the linguistic consciousness of Russians are caused to a greater extent by temporary rather than regional conditions.